The experiences and perceptions of newly qualified nurses in the UK: An integrative literature review. (July 2022) - Smythe, Analisa; Carter, Vanda
Abstract: Aim: This integrative review aimed to develop an understanding of the experiences and perceptions of newly qualified nurses in the United Kingdom (UK). Background: In the transitional period following registration, newly qualified nurses may feel socially isolated and overwhelmed by increases in accountability, workplace pressures and the psychological demands of the role. Despite this, the experiences and perceptions of newly qualified nurses remains an under-researched area in the UK, with much of the existing research having been conducted internationally. Method: An integrative framework methodology was used as a basis for the literature review. The methodology comprised of five stages: problem identification, literature search, data evaluation, data analysis and presentation of the findings. 20 papers were assessed for quality and analysed thematically. Results: Data were synthesised under four themes: Preparation for real-world practice, the transition experience, growing into the role and preceptorship and support from the wider team. Conclusion: The review suggests that newly qualified nurses require on-going support post qualification. Workplace culture appears to have a significant impact on the transition experience. The review provides further evidence in relation to the experiences of newly qualified nurses in the UK context. The review may help to inform the development of strategies to support and retain newly qualified nurses in an ever-changing health care environment.